Microwave ablation plus camrelizumab monotherapy or combination therapy in non-small cell lung cancer - Huang, Yahan; Wang, Jiao; Hu, Yanting; Cao, Pikun; Wang, Gang; Cai, Hongchao; Wang, Meixiang; Yang, Xia; Wei, Zhigang; Ye, Xin (Frontiers in Oncology, 2022)
Purpose: Immunotherapy has become widely applied in non-small cell lung cancer (NSCLC) patients. However, the relatively low response rate of immunotherapy monotherapy restricts its application. Combination therapy improves the response rate and prolongs patient survival; however, adverse events (AEs) associated with immunotherapies increase with combination therapy. Therefore, exploring combination regimens with equal efficacy and fewer AEs is urgently required. The aim of this study was to evaluate the efficacy and safety of microwave ablation (MWA) plus camrelizumab monotherapy or combination therapy in NSCLC. Materials and Methods: Patients with pathologically confirmed, epidermal growth factor receptor/ anaplastic lymphoma kinase-wild-type NSCLC were retrospectively enrolled in this study. Patients underwent MWA to the pulmonary lesions first, followed by camrelizumab monotherapy or combination therapy 5–7 days later. Camrelizumab was administered with the dose of 200 mg every 2 to 3 weeks. Treatment was continued until disease progression or intolerable toxicities. The technical success and technique efficacy of ablation, objective response rate (ORR), progression-free survival (PFS), overall survival (OS), complications of ablation, and AEs were recorded. Results: From January 1, 2019 to December 31, 2021, a total of 77 patients underwent MWA and camrelizumab monotherapy or combination therapy. Technical success was achieved in all patients (100%), and the technique efficacy was 97.4%. The ORR was 29.9%. The PFS and OS were 11.8 months (95% confidence interval, 9.5–14.1) and not reached, respectively. Smoking history and response to camrelizumab were correlated with PFS, and response to camrelizumab was correlated with OS in both the univariate and multivariate analyses. No periprocedural deaths due to ablation were observed. Complications were observed in 33 patients (42.9%). Major complications included pneumothorax (18.2%), pleural effusion (11.7%), pneumonia (5.2%), bronchopleural fistula (2.6%), and hemoptysis (1.3%). Grade 3 or higher AEs of camrelizumab, including reactive capillary endothelial proliferation, fatigue, pneumonia, edema, and fever, were observed in 10.4%, 6.5%, 5.2%, 2.6%, and 2.6% of patients, respectively. Conclusion: MWA combined with camrelizumab monotherapy or combination therapy is effective and safe for the treatment of NSCLC.